New Species of Neoperla Needham and Phanoperla Banks (Plecoptera: Perlidae) from the Philippine Islands - Sivec, Ignac (Illiesia, 2011)
Five new species of genus Neoperla Needham and three new species of genus Phanoperla Banks are proposed from specimens collected from Palawan and Mindanao in the Philippine Islands. New taxa include Neoperla agtouganon sp. n., N. andreas sp. n., N. palawan sp. n., N. sabang sp. n., N. salakot sp. n., Phanoperla batac sp. n., P. circumspina sp. n. and P. magnaspina sp. n. Additional records are given for N. dentata Sivec, 1984, N. nishidai Sivec, 1984 and N. pseudorecta Sivec, 1984, and one unassociated female is described under informal designation.
Keywords: entomologija; entomology; Plecoptera; vrbnice; nove vrste; Neoperla; Filipini; Phanoperla; stonefly; new species; Philippines